Fetal pericallosal lipomas – Clues to diagnosis in the second trimester. (November 2018) - Shinar, Shiri; Lerman-Sagie, Tally; Telleria, Monica Echevarria; Viñals, Fernando; García, Raquel; Quiroga, Hector; Bermejo, Carmina; Ben-Sira, Liat; Leibovitz, Zvika; Har-Toov, Joseph; Malinger, Gustavo
Abstract: Introduction: Pericallosal lipomas (PCL) are congenital soft masses of adipose cells encapsulated by a thin layer of fibrous tissue, appearing adjacent to the corpus callosum (CC). The lipomas are usually diagnosed prenatally during the third trimester. The purpose of this study was to identify 2nd trimester ultrasound findings that may hint to a later diagnosis of PCL and to evaluate their MRI evolution. Methods: A multicenter study of fetuses diagnosed during the 3rd trimester with a PCL in 7 fetal ultrasound units between 2001 and 2017. We reevaluated the ultrasound and MRI images starting from the referral examination and until the time of diagnosis, searching for clues that could have prompted an earlier diagnosis. Parents were contacted at the end of the study period to obtain information regarding development and neurological examination. Results: Fifteen patients with PCL were diagnosed during the study period; fourteen had second trimester scans. A 2nd trimester diagnosis was established in only 2 (13.3%). Anomalies of the CC were evident in 8/14 patients during the 2nd trimester scan and included: short length (n = 4), increased thickness (n = 1), complete agenesis (n = 2) and partial agenesis (n = 1). Third trimester ultrasound scans were considered diagnostic of PCL in all 12 remaining cases, in eight it was considered an isolated finding. Postnatal neurological evaluation in the isolated cases revealed normal development in all children. One child was diagnosed with attention deficit disorder. Conclusions: Non visualization of a PCL during the 2nd trimester is common, and should not be considered a diagnostic error. An underlying PCL should be included in the differential diagnosis of CC anomalies during this time period, necessitating further follow up into the 3rd trimester. Highlights: The diagnosis of a pericallosal lipoma may be missed during the 2nd trimester. An abnormal corpus callosum in the 2nd trimester raises the possibility of a pericallosal lipoma. Third trimester follow up is recommended before prognosis of can be determined. An isolated pericallosal lipoma is associated with a favorable neurological outcome.